EstudaJunto UFMG: um aplicativo móvel de encontros e coprodução para estudos na universidade - Luiz Paulo Damilton Corrêa (2017)
The widespread use of communication mobile devices has provided new forms of social interaction, from virtual relationships to real interactions. Using mobile applications, people are contacting others, including strangers, to meet and perform offline activities together. When there is a reciprocal collaboration, in which all involved are equally benefited, and roles of provider and recipient are not necessarily defined, the activity can be called as coproduction. In order to investigate how coproduction can be mediated by a mobile application and what are the aspects of this mediation considering a specific community and activity, this dissertation presents a case study, exploring the design of a mobile application directed to an academic purpose: StudyTogether UFMG (EstudaJunto UFMG, in Portuguese). The application intends to enable meetings among students, assisting them in their academic activities in pairs or in groups. During development, coproduction and its peculiarities in this field are discussed from the following stages: (1) identification and definition of students’ needs about group study activities, from interviews (10 people) and analysis via UDUM (Underlying Discourse Unveiling Method); (2) design and development of an interactive version in Android of StudyTogether UFMG; and (3) evaluation with users (12 people) using ISIM (Intermediated Semiotic Inspection Method). From the results of these stages, it was possible to raise and discuss relevant attributes to this type of application, performing a characterization that aim to be used as a guide for new projects. Also the academic context was explored and an application to assist the formation of groups in an university was proposed.